Upaya Penataan dan Pengelolaan Masalah Sampah di Desa Ranuklindungan Melalui Program CSR SUROPATI Oleh PT Indonesia Power Grati POMU - Khayubi, Achmad; Asmadi, Muhammad; Adhi, Bangkit Kresna; Gunawan, Uga Pratama (HK-Publishing, 2022)
Waste has become a serious problem for anyone in Pasuruan Regency. Waste becomes a problem when it is not managed properly. On the other hand, waste can also become people's income and fertilize plants if managed properly. PT Indonesia Power Grati POMU with a community empowerment program called SUROPATI in Ranuklindungan Village, Grati District, Pasuruan Regency. The research method used is qualitative research in Ranuklindungan Village, Grati District, Pasuruan Regency. Data collection was done by field observations, interviews and documentation. The data analysis used is interactive data analysis. The SUROPATI program in Ranuklindungan Village is an integrated waste management program. It is carried out with a social approach, a technical approach and an economic approach. This program has a positive impact on reducing the waste problem and economic impact. As the program progressed, an innovation in the manufacture of liquid organic fertilizer was born, namely Jlofer.